Indonesia Sunan Drajat Dalam Kajian Teori Konstitusi Nusantara - Sudrajat, Hendra (Program Studi Hukum Tata Negara dan diterbitkan oleh Program Studi Hukum Tata Negara dan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Sunan Drajat Lamongan, 2023)
This research provides a narrative on the solution to the current problems of national and state life, in which the phenomenon of disorientation in the life of the nation and state occurs which is marked by the emergence of an exemplary crisis in the state that has multidimensional impacts on constitutional life. The birth of the theory of the archipelago constitution provides a new narrative to explore the wisdom of the archipelago in the past constitutionally. One of the important messages presented in the theory of the constitution of the archipelago is the existence of Sunan Drajat who has left the exemplary footprint of the state and has relevance to the life of the nation and state today and in the future. The research method used in this study is legal history combined with state theory from several experts, with the grand theory of the archipelago constitution. This research first examines the value of Sunan Drajat's transformation in the life of the nation and state. The second is the application of Sunan Drajat's transformation values ​​in the life of the nation and state. The purpose of this study is to determine the value of Sunan Drajat's transformation in the life of the nation and state and its application in the contemporary context.